Contemporary research methods in business - Ye, Choy Leong; Choo, Wei Chong; Mak, Kit Mun; Lin, Woon Leong (Universiti Putra Malaysia Press, 2018)
In this book, a few contemporary research methods in business are introduced to researchers who are doing research in business. The concept and underlying philosophy of these methods are illustrated. The steps and application examples are also provided. We believe these contemporary research methods would enrich the research community. This book is suitable for university professors, lecturers and research students who want to pick up some new methods for their research work.